2011
DOI: 10.1007/s15010-011-0204-7
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to guidelines for antibiotic prophylaxis in surgery patients in German hospitals: a multicentre evaluation involving pharmacy interns

Abstract: The study revealed that many patients do not receive the appropriate antibiotic prophylaxis despite the fact that guidelines are in place. Based on these results, we conclude that PIs may play an important role in antibiotic prophylaxis management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
5
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 23 publications
4
53
5
6
Order By: Relevance
“…, Tourmousoglou et al 16 , Pitallis et al 15 and Hohmann et al 25 showed contrasting results with the present study, the values being 5.8%, 20%, We must note the current trend of antibiotic prophylaxis restricted to surgical time 9 .…”
contrasting
confidence: 77%
See 2 more Smart Citations
“…, Tourmousoglou et al 16 , Pitallis et al 15 and Hohmann et al 25 showed contrasting results with the present study, the values being 5.8%, 20%, We must note the current trend of antibiotic prophylaxis restricted to surgical time 9 .…”
contrasting
confidence: 77%
“…The result of multivariate analysis suggests that the outcome could not be associated with any independent variable, since there was no significant variability in this outcome frequency, that is, discontinuation of the antibiotic was performed in due time in most patients (95.7% cases). However, Wright et al 27 noted that groups of patients who more often received antibiotics for a long time were those with more comorbidities or elderly females.Surgical antibiotic prophylaxis may be considered appropriate when it reaches values of the criteria established in the adopted protocols close to 100%.From 11 analyzed articles that addressed appropriate surgical antibiotic prophylaxis, this parameter was considered inadequate in 100% of them [14][15][16][17]20,21,[23][24][25]28,30 . In their systematic review of adherence to surgical antibiotic prophylaxis protocols, Gouvêa et al 35 concluded that all the studies reviewed indicated the need for greater adherence to such protocols.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical site infections (SSI), one of the most common causes of nosocomial infections are a common complication associated with surgery, with a reported incidence rates of 2-20% [1]. They are responsible for increasing the treatment cost, length of hospital stay and significant morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Despite application of modern approaches of preoperative preparation of patient for surgery, antibiotic prophylaxis, and technological advances in infection control and operative techniques, wound infections after surgery still remains a major problem with its reported incidence varies from 2-20%. 1,2 It not only leads to patient discomfort and increasing morbidity but also responsible for prolong hospitalization thereby significantly increase the cost of treatment. 3 One data from United States mention 2% of their patients developed wound infection among the 40 million inpatient surgeries and more than 31 million day case or outpatient surgeries performed every year.…”
Section: Skin Acts As First Line Of Defense Against Infectionsmentioning
confidence: 99%